Evaluation of Hibiscus Sabdariffa L. calyx as cardioprotective agents - Asri, Nur Ain Mohd (2021)
Cardiovascular diseases (CVD), particularly Myocardial Infarction (MI), are the leading cause of mortality and morbidity worldwide. Hypercholesterolaemia increased the risk of developing CVD. Hibiscus sabdariffa L. (Roselle) has been used traditionally to reduce cholesterol levels. However, there is limited evidence of the plant's cardioprotective effects. The present study evaluated the effects of the aqueous extract of H. sabdariffa calyx (AEHS) on hypercholesterolaemia-myocardial infarction (HC-MI) rats. The proximate analysis was conducted to determine the nutritional composition of a self-made high-cholesterol diet (HCD). There are three phases in the animal study. The first phase (induction phase) was aim to develop an HC rat model using HCD for 6 weeks. The second phase (intervention phase) was to evaluate the effects of 30 days of AEHS treatment on body mass index (BMI), fasting blood sugar (FBS), fasting cholesterol (FC) and systolic blood pressure (SBP) in the rat. The third phase is where isoprenaline induced the myocardial infarction in rats (HC-MI) at day- 29 and 30. Although the cholesterol level was normal in HC-MI rats, there was a fatty change in the liver (steatosis). The HC-MI rat was also established based on raised cardiac troponin T level and the necrotic changes on the left ventricle tissue. However, AEHS did not significantly improve the parameters in the intervention phase. Moreover, AEHS did not reduce the cardiac troponin T significantly compared to the untreated-HC-MI, which is concurrent with the histology of the left ventricle. However, RFT and LFT were normal in AEHS-treated HC-MI. Collectively, further studies are needed to elucidate H. sabdariffa as a cardioprotective agent.